1975
DOI: 10.1111/j.1151-2916.1975.tb18990.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron and Carbon on Sintering of SIC

Abstract: PURE covalent solids, e.g. B, Si, C, Sic, and BN, cannot be densified by either sintering or conventional hot-pressing . However, some of these covalent solids can be densified in the presence of liquid-forming additions. For example, appreciable densification has been obtained in S&N, sintered with MgO' and YzO, + SO,?In Sic, liquid sintering has been observed in the presence of a B,C-Sic eutectic3 and in a melt of a composition in the system Al-B-C-Si.4 With liquid-phase sintering, however, only limited dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(98 citation statements)
references
References 2 publications
4
85
0
2
Order By: Relevance
“…proposed that boron and carbon could produce a driving force for diffusional mass transport necessary for sintering, by reducing the grain boundary energy [47]. This assumption was confirmed by other groups in the following years.…”
Section: Mechanism For Al B and C Effects On Grain Morphology Develosupporting
confidence: 73%
See 2 more Smart Citations
“…proposed that boron and carbon could produce a driving force for diffusional mass transport necessary for sintering, by reducing the grain boundary energy [47]. This assumption was confirmed by other groups in the following years.…”
Section: Mechanism For Al B and C Effects On Grain Morphology Develosupporting
confidence: 73%
“…In addition, Rijswijk et al reported that carbon reduces the loss of boron in the SiC lattice [46]. Therefore, the boron and carbon appear to have similar promotional effects on the β-to-α phase transformations as observed in the present study as well as discussed in other publications [46,47], but the effect of boron is more pronounced. It can be concluded that boron and carbon are key elements in inducing β-to-α phase transformations in SiC.…”
Section: H-sicsupporting
confidence: 56%
See 1 more Smart Citation
“…Later, it was found that hot pressing with boron and carbon additions could lead to a SiC with 96% of the theoretical density [2], or better [3][4]. While the densification mechanism was not clear, it was already known that boron and carbon did not form intergranular films [5][6] but rather dissolved into the SiC grains, not supporting a liquid phase densification mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Al-based oxycarbide grain boundary film between SiC grains were observed [2,7,[17][18][19][20][21][22], as well as other secondary phases at triple junctions [21][22][23]. The best of these SiC materials yet investigated exhibited unprecedented combinations of strength, fracture toughness, fatigue, high temperature creep resistance, and wear resistance [9,14,17,18,[24][25][26][27][28][29][30][31], resulting from the presence of favorable grain boundary structures [22].…”
Section: Introductionmentioning
confidence: 99%